The mediating role of impulsivity between sleep quality and suicidal ideation in adolescent population: a multicenter cross-sectional study in the northeastern Sichuan, China - Zhong, Yunling; He, Jinlong; Luo, Jing; Zhao, Jiayu; Cen, Yu; Wu, Yuhang; Song, Yuqin; Lin, Cen; Pan, Lu; Luo, Jiaming (Frontiers in Psychiatry, 2024)
Introduction Suicidal ideation is a critical early stage in the progression towards suicidal be havior. Prior research has established links between sleep quality, impulsivity, and suicidal tendencies, yet the interaction among these factors has been less explored. This study aims to explore the mediating role of impulsivity in the relationship between sleep quality and suicidal ideation in adolescents. Methods Employing a cross-sectional study design, 6,974 questionnaires were distributed,including the Socio-demographic Characteristics Questionnaire, Barratt Impulsiveness Scale, the Positive and Negative Suicide Ideation Inventory,and the Pittsburgh Sleep Quality Index Scale. The participants were high school and middle school students from 33 schools in northeastern Sichuan, China, selected through random cluster sampling. Results Of these 6,786 questionnaires were analyzed. The participant distribution included 47.2% male and 52.8% female students, with 68.3% from junior schools and 31.7% from senior schools. The prevalence of suicidal ideation was found to be 13.6%. The analysis, which involved correlation analysis and the construction of a structural equation model, revealed that sleep quality had a significant positive effect on impulsivity (β:0.289,p < 0.05), and impulsivity, in turn, had a positive impact on suicidal ideation (β:0.355,p < 0.05).Moreover, sleep quality was directly linked to suicidal ideation (β:0.208,p < 0.05). Thus, sleep quality affects suicidal ideation both directly and indirectly through impulsivity. Discussion The results of this study suggest that both sleep quality and impulsivity are significant direct influencers of suicidal ideation among adolescents in the region studied, with impulsivity also playing an indirect role in the relationship between sleep quality and suicidal ideation.